2014
DOI: 10.1039/c4sm00556b
|View full text |Cite
|
Sign up to set email alerts
|

Two coupled effects of sub micron silica particles on the mechanical relaxation behavior of ethylene–propylene–diene rubber chains

Abstract: This article studied the influence of silica (SiO2) particles on the crosslinked network and the molecular mobility of ethylene-propylene-diene (EPDM) rubber chains by dynamic mechanical analysis (DMA). When SiO2 fraction is lower than 8 phr, the chain segments that participate in the glass-rubber transition (α transition) decrease with increasing the SiO2 content, while the whole crosslinked network is almost unaffected by the presence of SiO2. When the SiO2 fraction increases to about 20 phr, there appears a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…For example, the DSC results showed that the T g increased from −65.3°C of the neat DPNR to −62.3°C of the HP‐DPNR/CS 7 . This phenomenon can be explained by the restriction of rubber chain mobility by CS framework 40,41 . Such slight increase of T g was also reported in some studies that adding chitosan into NR 3,42 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…For example, the DSC results showed that the T g increased from −65.3°C of the neat DPNR to −62.3°C of the HP‐DPNR/CS 7 . This phenomenon can be explained by the restriction of rubber chain mobility by CS framework 40,41 . Such slight increase of T g was also reported in some studies that adding chitosan into NR 3,42 .…”
Section: Resultssupporting
confidence: 70%
“…This phenomenon can be explained by the restriction of rubber chain mobility by CS framework. 40,41 Such slight increase of T g was also reported in some studies that adding chitosan into NR. 3,42 Similarly, the HP-DPNR/CS also showed a certain resistance to the solvent due to the restriction of rubber chain mobility by CS framework.…”
Section: Preparation Of Hp-dpnr/cs Films and Their Structural Charact...supporting
confidence: 72%
“…Figure S3 shows that the soluble fraction F s and the swelling ratio Q decreased with increasing cross-linking agent amounts, which indicates PDMS becomes more cross-linked. 31 To further investigate the relevance between adhesion force and different cross-linking density, we tested the evolution of adhesion force (F) under different retract speeds (Figure 3c). When the cross-linking agent content decreased, the increase of retract speed (ν) during high retract speed (F ∝ ν β ) can cause more increase of the adhesion force (F), from ν 15.9 for the PDMS with 9.1 wt % of cross-linking agent to ν 50.4 for the PDMS with 2.0 wt % of cross-linking agent as the inset shows.…”
Section: Resultsmentioning
confidence: 99%
“…The soluble fraction F s and the swelling ratio Q are calculated from the relations as follows in which ρ polymer and ρ toluene are the density of the PDMS and the toluene, respectively. Figure S3 shows that the soluble fraction F s and the swelling ratio Q decreased with increasing cross-linking agent amounts, which indicates PDMS becomes more cross-linked . To further investigate the relevance between adhesion force and different cross-linking density, we tested the evolution of adhesion force ( F ) under different retract speeds (Figure c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…6 Elastomer is a typical kind of visco-elastic materials, attributed to the viscous friction between molecules. 7 For the practical application of automobile tires, nano-sized NPs such as carbon black [8][9][10] or silica [11][12][13] are always introduced to improve the mechanical properties through nanoreinforcement, such as the modulus, tensile and tear strength, abrasion resistance and so on. Since the loading of NPs is high, the aggregate of NPs always occur attributed to the weak interaction between NPs and elastomer, strong van der Walls interaction between NPs and the loss of the conformational entropy of polymer chains in the vicinity of NPs.…”
Section: Introductionmentioning
confidence: 99%